Partisipasi Masyarakat Dalam Pengelolaan Desa Wisata Tista - Wijana, Putu Ade; Damayanti, Luh Sri (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2021)
Rural tourism becomes a new trend in the tourism industry. There are many villages in Bali that are developing themselves to be tourism destinations. One of them is Desa Wisata Tista in Tabanan Regency, Bali. This village has become a tourism destination in Tabanan and many tourists visited this village. However, research showed that the management of Desa Wisata Tista has not been done maximally. This current research aimed at observing and analyzing the community’s participation in managing the Desa Wisata Tista. This was done as qualitative research in which the data were gained through an interview with the chief of management or in Bahasa it is called kelompok sadar wisata. The results of the interview reveal that the community participates well in the management of Desa Wisata Tista. Participation is done directly and indirectly. Direct participation is done by involving themselves in the management group, meanwhile, indirect participation is done by maintaining the cleanliness and safety of the environment which bring a big impact on the tourists’ comfort. It is suggested to improve the community’s participation by involving more in the management groups as well as become employees in the tourist attractions in Desa Wisata Tista.    Keywords : rural tourism, tourism destination, community tourism